2010
DOI: 10.1266/ggs.85.259
|View full text |Cite
|
Sign up to set email alerts
|

Molecular evidence that most RNAs required for germination and pollen tube growth are stored in the mature pollen grain in petunia

Abstract: After landing on the stigma, the pollen grain germinates and elongates a tube to deliver its generative nuclei to the egg cell of the ovule. The molecular mechanisms involved in the drastic morphological changes in the pollen grain during this fertilization process remain largely unknown. In this study, the expression of 732 randomly selected genes in petunia pollen and pollen tubes was analyzed by microarray and quantitative PCR analyses. We found no evidence for upregulation of any of these genes in the poll… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
6
0

Year Published

2012
2012
2020
2020

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(6 citation statements)
references
References 22 publications
0
6
0
Order By: Relevance
“…Unfortunately, in contrast to IR‐induced damage of the chromatin, IR‐effects on the cellular RNA‐entity have gained little attention, and a direct experimental comparison of the collective DNA‐ and RNA‐stability towards IR has not been drawn. Assumed that single RNA molecules are less affected by IR than the massive genomic DNA, then the above observation would correlate with the hypothesis that germination and early tube growth depend on pre‐generated RNAs stored in the mature pollen, whereas subsequent tube elongation depends on synthesis of novel RNAs (Fernando et al, 2001; Hao et al, 2005; Ishimizu et al, 2010). In this special scenario all processes, viz., germination, early as well as continued tube growth would depend on those stored RNAs withstanding IR‐treatment in the mature pollen, because synthesis of novel RNA would be inhibited by preceding IR‐induced deterioration of the genome.…”
Section: High Dose Ir‐effects On Pollen Germination and Tube Growthmentioning
confidence: 87%
See 1 more Smart Citation
“…Unfortunately, in contrast to IR‐induced damage of the chromatin, IR‐effects on the cellular RNA‐entity have gained little attention, and a direct experimental comparison of the collective DNA‐ and RNA‐stability towards IR has not been drawn. Assumed that single RNA molecules are less affected by IR than the massive genomic DNA, then the above observation would correlate with the hypothesis that germination and early tube growth depend on pre‐generated RNAs stored in the mature pollen, whereas subsequent tube elongation depends on synthesis of novel RNAs (Fernando et al, 2001; Hao et al, 2005; Ishimizu et al, 2010). In this special scenario all processes, viz., germination, early as well as continued tube growth would depend on those stored RNAs withstanding IR‐treatment in the mature pollen, because synthesis of novel RNA would be inhibited by preceding IR‐induced deterioration of the genome.…”
Section: High Dose Ir‐effects On Pollen Germination and Tube Growthmentioning
confidence: 87%
“…It should be highlighted that pollen tubes are the fastest growing cell type currently known and their polar cell growth is a highly susceptible process which requires a proper functioning molecular network facilitating the correct sequence of intracellular events (Hepler & Winship, 2015; Scheible & McCubbin, 2019; Stephan, 2017). In this context, germination and early tube growth of ‘natural’ non‐irradiated pollen are considered to be independent of novel RNA synthesis and thus these processes require stored RNA and stored proteins (Dai et al, 2007; Fernando, Owens, Abul, & Ekramoddoullah, 2001; Hao, Li, Hu, & Lin, 2005; Ishimizu, Kodama, Ando, & Watanabe, 2010; Noir, Brautigam, Colby, Schmidt, & Panstruga, 2005; Roberts, Harrod, & Dickinson, 1984). However, during continued pollen tube growth, particularly in vivo in the style tissue (progamic phase), the expression of a significant number of genes is upregulated (Hafidh et al, 2012; Hafidh, Breznenova, & Honys, 2012; Qin et al, 2009).…”
Section: High Dose Ir‐effects On Pollen Germination and Tube Growthmentioning
confidence: 99%
“…It is commonly accepted that most plants accumulate mRNAs and proteins in their mature pollen until the time of germination and thus do not require transcription during elongation. For example, recent data show that most of the RNAs required for germination and pollen tube growth are stored in the mature pollen grain in Petunia , so de novo transcription may not be necessary (Ishimizu et al 2010 ). However, in vitro studies have suggested that de novo mRNA synthesis does occur during pollen germination and tube elongation (see review by Huang et al 2011 ).…”
Section: Discussionmentioning
confidence: 99%
“…These differences are probably due to different pollen harvesting methods, different Arabidopsis accessions, and different algorithms used for decision on presence or absence of expression. Microarrays were also used for transcriptional profiling of mature pollen from maize, soybean (Glycine max) and Petunia axillaries, and uninucleate microspores, bicellular and tricellular pollen from rice (Table 1, Figure 2; Ma et al, 2008;Haerizadeh et al, 2009;Ishimizu et al, 2010;Wei et al, 2010). Apart from this, genes expressed in the generative cell from L. longiflorum have been identified using cDNA microarrays (Table 1; Okada et al, 2007).…”
Section: Increasing Estimates Of Transcriptome Size Of the Germline Lmentioning
confidence: 99%